2001
DOI: 10.1053/jhep.2001.25225
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection: A hidden menace?

Abstract: Recovery from an acute hepatitis B virus (HBV) infection is associated with loss of HBV DNA from serum, hepatitis B e antigen seroconversion, hepatitis B surface antigen (HBsAg) seroconversion, and normalization of serum aminotransferases. These changes generally imply clearance of virus, but clinical observations have shown that reactivation of HBV infection can occur either spontaneously or after immunosuppression. [1][2][3] Recent studies showed that immune response to HBV remains vigorous long after an acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
100
1
5

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(110 citation statements)
references
References 24 publications
4
100
1
5
Order By: Relevance
“…HBV DNA levels in most of the individuals of this study with occult HBV infection was 10 2 -10 3 copies/ml, which is in accordance with the HBV DNA levels reported by Conjeevaram and Lok [2001] and well below the cut-off level proposed by NIH Workshop on HBV consensus 2000. Moreover, nested PCR is a cumbersome method and prone to contamination especially for cases with HBV DNA below 10 3 copies/ml.…”
Section: Discussionsupporting
confidence: 90%
“…HBV DNA levels in most of the individuals of this study with occult HBV infection was 10 2 -10 3 copies/ml, which is in accordance with the HBV DNA levels reported by Conjeevaram and Lok [2001] and well below the cut-off level proposed by NIH Workshop on HBV consensus 2000. Moreover, nested PCR is a cumbersome method and prone to contamination especially for cases with HBV DNA below 10 3 copies/ml.…”
Section: Discussionsupporting
confidence: 90%
“…3 Since HBV DNA level is usually less than 10 3 copies/mL in occult HBV infection, the detection of occult infection is strongly dependent on both the sensitivity and specificity of the assay. 15 Occult HBV infection is more frequently reported in the countries with high HBV infection, such as China, Japan and Taiwan, compared with Western countries. 6,11 South Korea is still an endemic area for HBV infection, and Kim et al 16 reported the prevalence of occult HBV infection was high (16%) in HBsAg negative subjects with normal serum ALT levels in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…5 This so-called occult HBV infection has been identified by sensitive polymerase chain reaction (PCR) assays that detect low levels of HBV DNA in serum and/or liver tissue of HBsAg-negative subjects. [6][7][8] Since the early 1980s, several studies have reported the detection of HBV DNA in both tumorous and non-tumorous liver tissue of HBsAg-negative HCC patients. 9,10 However, whether occult HBV infection also contributes to the pathogenesis of HCC remains unclear.…”
mentioning
confidence: 99%